Phytochemical screening, FT-IR analysis and antimicrobial activity of Wattakaka volubilis - Selvaraj, Venkatesan; M., Anithakumari; V., Balamurugan; Arjunan, Sundaresan; Perumal, Susindren; K., Vasanthi (International Journal of Biological Research, 2016)
The present study was evaluated the phytochemical analysis and antibacterial activity of Wattakaka volubilis leaf extract. The Wattakaka volubilis is medicinal plant used in the treatment of various diseases (Wound, diabetics, rheumatic and diarrhea). The ethanol, methanol, petroleum ether and DMSO extract from the leaf of Wattakaka volubilis were screened on their phytochemicals analysis. Among thesePhytochemicals were alkaloids, anthroquione, caumarin, flavanoids, phenols, saponins, steroids, tannins and terpenoids for present in the following extracts ethanol, methanol. The petroleum ether and DMSO only present in several phytochemicals like alkaloid, anthroquinone, terpenoids and tannins. Wattakaka volubilis against the antibacterial like E. coli, B. pumilus, Enterobacter aerogens, and Pseudomonas aeruginosa. The zone of inhibition of Wattkaka voulubilis leaf extract against the bacteria was maximum inhibition Pseudomonas aeruginosa, Enterobacter aerogens, Bacillus pumilis. The least zone of inhibition was recorded against E.coli. The characterization of the plant extract and the functional groups was analyzed in Fourier Transform Infrared Spectroscopy (FTIR). The absorbance bands analysis were observed in the region of 4000-400cm-1 are 23 compounds derived. The compounds represented the ranges from 3905.21 to 436.41 peaks were shown. This study which is the primary report on the phytochemicals analysis and antibacterial properties of Wattakaka volubilis supports its traditional uses in the treatment of infectious and non- infectious diseases.
Keywords: Wattakaka volubilis; Phenols; Ethanol; DMSO; Bacillus Pumilus; Bacteria; Tannin Etc.